Effect of The Combination of Protected and Non-Protected Soybean Oil (Glycine max L.) Supplementation on Characteristics of Rumen Fermentation, Nutrient Digestibility, and Nitrogen Balance in Garut Sheep - Muhammad Luqmanul Hakim; Chusnul Hanim; Lies Mira Yusiati (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
Soybean oil is a high source of unsaturated fatty acids which if given to sheep have the potential to accumulate in the meat. However, in the rumen unsaturated fatty acids undergoes biohydrogenation by rumen microbes, and the addition of fat in the feed has the potential to reduce fiber fermentation in the rumen which can have an impact on animal performance. This study aimed to determine the effect of the combination of protected and non-protected soybean oil supplementation on the characteristics of rumen fermentation, nutrient digestibility, and nitrogen balance of Garut sheep. Twelve male Garut lambs aged 13 months and weighing 29±3.23 kg were kept in a metabolic cage and divided into three groups. The basal diet of 60% King grass and 40% pollard bran was supplemented with protected and non-protected soybean oil with the ratio of 3%:0%, 1.5%:1.5%, and 0%:3%, respectively, based on the dry matter of ration. The data obtained were analyzed by One-Way ANOVA, followed by the Duncan Multiple Range Test (DMRT). The results showed that supplementation had no effect on rumen fatty acids profile, microbial protein, ammonia concentration, total volatile fatty acids, acetat, propionate, butirat, and pH. The digestibilities of dry matter, organic matter, crude protein, crude fibre, and crude fat were not affected. Supplementation also had no effect on nitrogen balance. Hence supplementation of different levels of protected fats did not influence animal performance in Garut sheep.